1298. Acquisition of TDF-Susceptible HIV Despite High Level Adherence to Daily TDF/FTC PrEP as Measured by Dried Blood Spot (DBS) and Segmental Hair Analysis: A Case Report. (26th November 2018) - Cohen, Stephanie E; Sachdev, Darpun; Lee, Sulggi; Scheer, Susan; Bacon, Oliver; Chen, Miao-Jung; Norvell, Clarissa Ospina; Okochi, Hideaki; Anderson, Peter; Coffey, Susa; Scott, Hyman; Havlir, Diane; et al.
Abstract: Background: Pre-exposure prophylaxis (PrEP) with emtricitabine/tenofovir (TFV) disoproxil fumarate (FTC/TDF) is highly protective against HIV infection. We report the second case of acquisition of TDF-susceptible HIV despite high adherence to PrEP, confirmed by drug level testing. Methods: PrEP adherence was assessed by measuring FTC/TDF metabolites in dried blood spots (DBS) and FTC/TFV concentrations in segments of scalp hair. Genotypic and phenotypic resistance were evaluated. HIV partner services (PS) and HIV sequences reported to HIV surveillance with a genetic distance ≤1.5% (by HIV-Trace) identified likely transmission partners. Results: A 21-year-old Latino man presented 13 months after PrEP initiation. He was HIV negative by rapid HIV antibody (Ab) and HIV RNA pooling (detection limit 40 copies/mL) at PrEP initiation and at months 3, 6, and 10. At the 13-month visit, he was asymptomatic and his rapid HIV Ab was negative. Five days later, his HIV RNA was reported as positive (559 copies/mL). He was notified of the result, linked to care and immediately started antiretroviral treatment (ART), at which point his RNA was 1544 copies/mL and his HIV Ab test was positive. The HIV genotype had M184V, L74V and K103N mutations and phenotypic susceptibility to TDF. TFV/FTC levels by LC-MS/MS measured in 1 cm segments of hair collected at ART initiation indicated consistently high PrEP adherence in each of the preceding 6 months. TFV-diphosphate and FTC-triphosphate levels in DBS collected 2 days after ART initiation were 1012 fmol/punch and 0.266 pmol/punch, confirming high adherence over the preceding 6 weeks. Between PrEP initiation and HIV acquisition, he had 1 episode of urethral chlamydia and three episodes of urethral gonorrhea. The likely transmission partner, named during PS, had no history of viral suppression in HIV surveillance and harbored the same resistance mutations, with a genetic distance between the two patients of 0.66%. The partner was re-linked to care and had a current HIV RNA of 15, 130 copies/mL. Conclusion: Acquisition of TDF-susceptible HIV infection can occur despite high PrEP adherence. Quarterly HIV and STD screening of patients on PrEP, combined with prompt linkage to care and PS for those diagnosed with HIV, facilitates early diagnosis and prevents further transmission of HIV. Disclosures: S. E. Cohen, Gilead: Investigator in PrEP study for which Gilead donated drug, donated study drug and paid for drug testing during the PrEP demo project, of which I was a co-PI (the study has ended). S. Lee, Viiv Healthcare: Investigator, Research grant. Gilead Sciences: Investigator, Research grant. P. Anderson, Gilead: Consultant and Investigator, funds were paid to the institution for contract work and grant support and Research support. D. Havlir, Gilead: Investigator, Gilead Sciences provides antiretroviral therapy for a NIH funded study that she is conducting and Research support.